A study on the relationship between work life culture and employees' satisfaction at Pejabat Daerah Marang / Nur Shakirah Azman - Azman, Nur Shakirah (Faculty of Business and Management, 2018)
The title of this study was to investigate the relationship between work life culture and employees' satisfaction. In this research paper, there were contained the details of the research such as the objectives of the research, the research question, the research design and others. This research was conducted at Pejabat Daerah Marang, Terengganu in a period from 11st September until 24th December 2017. In chapter one, the researcher has been explained about the background of the study, statement of the problem, research objectives, research questions, research hypothesis, significance of the study, limitations of the study and the definition of the term. For background of the study, the researcher explained a little about the study and for statement of the problem, the researcher stated the problems occurred if the organizations were not applied work-life culture in the organization. Next, in chapter one also, it has contained the objectives or the purpose of the research, listed research question that has been answered in chapter four. Furthermore, the research hypotheses were listed, significances of study were stated and definition of the terms that were used in this research. Besides, in chapter two were contained the literature review for every independent and dependent variables which were job sharing, childcare support, employees welfare, wellness program and employees satisfaction. The literature review mostly was about the definition of the factors and also the advantages and disadvantages of the factors. The ideas stated in literature review were supported by the citation from previous researcher